2018
DOI: 10.3389/fpls.2018.00049
|View full text |Cite
|
Sign up to set email alerts
|

Non-parent of Origin Expression of Numerous Effector Genes Indicates a Role of Gene Regulation in Host Adaption of the Hybrid Triticale Powdery Mildew Pathogen

Abstract: Powdery mildew is an important disease of cereals. It is caused by one species, Blumeria graminis, which is divided into formae speciales each of which is highly specialized to one host. Recently, a new form capable of growing on triticale (B.g. triticale) has emerged through hybridization between wheat and rye mildews (B.g. tritici and B.g. secalis, respectively). In this work, we used RNA sequencing to study the molecular basis of host adaptation in B.g. triticale. We analyzed gene expression in three B.g. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 63 publications
0
45
0
Order By: Relevance
“…To test if family members within clusters are co‐regulated, we analyzed expression patterns within and between candidate effector families. Here, we used published transcriptome data from isolate 96224 growing on the susceptible wheat cv Chinese Spring (Praz et al ., ) at 48 h post infection (when the haustorium is formed and the host–pathogen interaction is established). We observed a wide range of expression levels within individual families (Figs S3, S11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test if family members within clusters are co‐regulated, we analyzed expression patterns within and between candidate effector families. Here, we used published transcriptome data from isolate 96224 growing on the susceptible wheat cv Chinese Spring (Praz et al ., ) at 48 h post infection (when the haustorium is formed and the host–pathogen interaction is established). We observed a wide range of expression levels within individual families (Figs S3, S11).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore analyzed differential gene expression between three B.g. tritici isolates (96224, 94202, JIW2) on cv Chinese Spring, published in Praz et al (2018) at the time of haustorium formation (2 d after infection). Among the 339 differentially expressed genes between two isolates (|log FC| > 1.5 and P-value < 0.01), 87 are effector genes (25.7%, enrichment).…”
Section: Researchmentioning
confidence: 99%
“…This form of adaptation will lead to isolates with diverse transcriptional profiles, which could also have different fitness optima on the same host. Indeed, individual isolates of the same forma specialis of B. graminis show considerable differences in expression levels of effector genes during infection (Praz et al, 2018). Similarly, in Z. tritici, 20-30% of the genes are differentially regulated between individual isolates during infection of the same host, and are likely to account for the quantitative variation in virulence within this species (Palma-Guerrero et al, 2017).…”
Section: Transcriptional Plasticity In Stressful Environmentsmentioning
confidence: 99%
“…tritici infected seedlings at three dpi, a time point corresponding to the haustorial stage. Previous studies have shown that gene expression levels of SvrPm3 a1/f 1 are the highest during haustorium formation (Bourras et al, 2015(Bourras et al, , 2019Praz et al, 2018). Similarly, several members of the SvrPm3 a1/f 1 effector gene family, including Bgt_Bcg-6 and Bgt_Bcg-7, are induced at that same stage ( Supplementary Figure 4) (Praz et al, 2018;Bourras et al, 2019), suggesting that this time point is particularly appropriate for the quantification of mRNA levels of all three effectors, and to assess HIGS efficiency.…”
Section: The Svrpm3 A1/f 1 -Rnai Transgene Reduces Target Effector Gementioning
confidence: 82%
“…), HIGS is an important tool for functional genomics (Nowara et al, 2010;Pliego et al, 2013). In this system, successful infection is typically characterized by the formation of a highly specialized feeding structure called the haustorium, shortly after an appressorium-mediated penetration of the plant cell wall (Praz et al, 2018). The haustorium is a poorly understood membrane invagination that develops inside the host epidermal cell, and serves as a basis for the emergence of a network of strictly epiphytic hyphae which can form secondary appressoria (Kwaaitaal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%